Quantifying peat hydrodynamic properties and their influence on water table depths in peatlands of southern Quebec (Canada) - Bourgault, Marc‐André; Larocque, Marie; Garneau, Michelle; Roux, Marjolaine (Ecohydrology, 2018)
Abstract Water table depth in peatlands is strongly linked to physical properties of the peat, such as density (ρ dry ), peat composition and humification, hydraulic conductivity (K), and specific yield (S y ). Dry bulk density and peat depth are commonly used as indicators of K in ecohydrological models. However, no mathematical relationship exists to quantify S y based on K and ρ dry . As a result, ecohydrological models cannot explicitly reproduce the strong buffering capacity of peatlands. The objectives of this study were to analyse the literature‐reported mathematical link between all the physical properties to develop new mathematical relationships between these parameters and to evaluate whether variations in the physical properties of the peat control water table depth in peatlands. Seven peatlands located in the St. Lawrence Lowlands (Québec, Canada) were sampled, and 1 m long peat cores were collected from up‐gradient, mid‐gradient, and down‐gradient zones. All cores were used to measure ρ dry , K, S y , and to estimate peat composition and humification. Statistically significant correlations were found between (a) K and S y (log–log model), (b) K and depth (log–log model), (c) S y and depth (log–log model), (d) ρ dry and S y (log model), and (e) ρ dry and K (log model). No significant difference was found in either K or S y between sites. However, significant differences were found in water table depths. Because they provide a fuller description of the peat properties that control water table depths, these newly developed functions have the potential to improve the capacity of ecohydrological models to simulate time‐varying hydrological conditions.

Dynamics of groundwater floodwaves and groundwater flood events in an alluvial aquifer - Buffin-Bélanger, Thomas; Cloutier, Claude-André; Tremblay, Catherine; Chaillou, Gwénaëlle; Larocque, Marie (2016)
In gravelly floodplains, streamflood events induce groundwater floodwaves that propagate through the alluvial aquifer. Understanding groundwater floodwave dynamics can contribute to groundwater ﬂood risk management. This study documents groundwater floodwaves on a flood event basis to fully assess environmental factors that control their propagation velocity, their amplitude and their extension in the floodplain, and examines the expression of groundwater flooding in the Matane River floodplain (Quebec, Canada). An array of 15 piezometers equipped with automated level sensors and a river stage gauge monitoring at 15-minute intervals from September 2011 to September 2014 were installed within a 0.04-km2 area of the floodplain. Cross-correlation analyses were performed between piezometric and river-level time series for 54 flood events. The results reveal that groundwater floodwave propagation occurs at all flood magnitudes. The smaller floods produced a clear groundwater floodwave through the floodplain, while the largest floods affected local groundwater flow orientation by generating an inversion of the hydraulic gradient. Propagation velocities ranging from 8 to 13 m/h, which are two to three orders of magnitude higher than groundwater velocity, were documented while the induced pulse propagated across the floodplain to more than 230 m from the channel. Propagation velocity and amplitude attenuation of the groundwater floodwaves depend both on flood event characteristics and the aquifer characteristics. Groundwater flooding events are documented at discharge below bankfull (< 0.5 Qbf). This study highlights the role of flood event hydrographs and environmental variables on groundwater floodwave properties and the complex relationship between flood event discharge and groundwater flooding. The role that groundwater floodwaves play in flood mapping and the ability of analytical solutions to reproduce them are also discussed.